UCyt+/ImmunoCyt and cytology in the detection of urothelial carcinoma. Issue 7 (12th March 2013) - Comploj, Evi; Mian, Christine; Ambrosini‐Spaltro, Andrea; Dechet, Christopher; Palermo, Salvatore; Trenti, Emanuela; Lodde, Michele; Horninger, Wolfgang; Pycha, Armin
<x xml:space="preserve">Abstract</x> BACKGROUND The aim of the current study was to report the results of 7422 uCyt+/ImmunoCyt and cytology analyses that were performed over the course of 9 years at the study institution for the evaluation and follow‐up of patients with urothelial carcinoma. METHODS Between January 2002 and March 2011, 2217 patients with a mean age of 69.5 years (range, 15 years‐99 years) were enrolled in the current study. All patients seen for the follow‐up of bladder and/or upper tract urothelial cancer as well as those with a history that was suspicious for bladder cancer were recruited. In all patients, a voided urinary cytology and uCyt+/ImmunoCyt test was performed. Patients underwent routine cystoscopy as well as cystoscopy when cytology and/or the uCyt+/ImmunoCyt test yielded positive results. Lesions that were detected cystoscopically were biopsied and removed transurethrally. A total of 7422 uCyt+/ImmunoCyt and cytology analyses were performed. RESULTS Of the 7422 uCyt+/ImmunoCyt tests and cytologies that were performed, 7075 (95.3%) were considered adequate. A total of 578 patients (with 1156 analyses) underwent biopsy and 728 (63%) samples had a histologically proven urothelial carcinoma. Overall sensitivity was 34.5% for cytology, 68.1% for uCyt+/ImmunoCyt, and 72.8% for the 2 tests combined. Overall specificity was 97.9% for cytology, 72.3% for uCyt+/ImmunoCyt, and 71.9% for the 2 tests combined. Cytology and the uCyt+/ImmunoCyt test together had an overall sensitivity of 72.8%, with 59% for grade 1, 77% for grade 2, and 90% for grade 3 tumors (according to the 1973 World Health Organization grading classification system). CONCLUSIONS On the basis of their 9‐year experience, the authors confirm the value of uCyt+/ImmunoCyt and cytology analyses in the follow‐up of patients with non–muscle‐invasive urothelial cancer. This could potentially reduce the number and cost of routine cystoscopic examinations in patients who are followed for bladder carcinoma. Cancer (Cancer Cytopathol) 2013;121:392–397. © 2013 American Cancer Society.